PMAIP1 regulates the progression of follicular thyroid carcinoma through the Wnt3/FOSL1 pathway - Wang, Haobo; Shang, Fangjian; Wang, Yifang; Pang, Bo; Kang, Longfei; Zhou, Chuanmin; Li, Dongyun; Li, Zhongxin; Jiang, Xia; Liu, Bo; Zhao, Zengren (Frontiers in Oncology, 2025)
IntroductionIn thyroid carcinoma (TC), follicular thyroid carcinoma (FTC) represents the second most prevalent pathological type following papillary thyroid carcinoma. Notably, FTC exhibits a more aggressive clinical course and a higher propensity for distant metastasis. However, the underlying mechanisms governing the progression of FTC remain poorly understood. PMAIP1 is a gene implicated in various cancers and biological processes. Investigating the role and mechanism of PMAIP1 in FTC is crucial for enhancing our understanding of FTC and informing clinical treatment strategies. MethodsThis study examined the expression level of PMAIP1 in FTC through comprehensive analysis of databases, tumor tissues, and cell lines. Following the establishment of a stably transfected plasmid in cell lines, a series of functional assays and subcutaneous xenograft experiment were conducted to investigate the role of PMAIP1 in FTC. Additionally, transcriptome sequencing was employed to identify potential signaling pathways associated with PMAIP1. Mechanistic studies involved a series of rescue experiments to elucidate the regulatory mechanisms of PMAIP1 in FTC. ResultsPMAIP1 was found to be highly expressed in FTC, and its knockdown significantly inhibited the proliferation and metastasis of FTC cells both in vivo and in vitro. The results of transcriptome sequencing analysis indicated that PMAIP1 may influence the progression of FTC via the Wnt signaling pathway. Subsequent investigations revealed a direct correlation between PMAIP1 expression levels and those of Wnt3 and FOSL1 in FTC. A series of rescue experiments further substantiated the regulatory role of PMAIP1 on Wnt3/FOSL1 in FTC. DiscussionIn conclusion, our research demonstrated that PMAIP1 emerges as a novel pro-cancer factor in FTC, and its knockdown significantly inhibited the proliferation and metastasis of FTC both in vivo and in vitro. Mechanistically, PMAIP1 regulated FOSL1 by modulating the Wnt signaling pathway, thereby promoting FTC progression. Targeting PMAIP1 may present a promising therapeutic strategy for FTC.